Aprendizagem profissional da docência : que saberes o(a) professor(a) tem para atuar em creches? - Voltarelli, Monique Aparecida (2013)
to teach and the importance of the teacher to keep learning are highlighted themes in order to comprehend the professional development and the teacher s education, although the aspects of caring and educating are still disconnected when we think about the pedagogical practices in kindergarten. Considering this, a qualitative approach of researching was adopted in three municipal kindergarten educational centers in the countryside of São Paulo, involving three beginner teachers, who work with children from zero to three years old. Considering the research question How is the beginning teachers` teaching knowledge configured to act in nursery care? , we tried to characterize the knowledge owned by the teachers who work with children from zero to three and how they learn to be nursery care teachers. In order to develop this study, field observations, diary registers, documental analyses and semi structured interview were undertaken. The collected data were organized in five axes of analyses in order to achieve the research s specific objectives: a) the teachers´ conception of nursery care and children; b) the kindergarten institutions´ pedagogical propose; c) the actions of educating and caring; d) the contents taught to children from 0 to 3; e) the learning of teaching in the nursery care. The analyses according to authors as Abramowicz, André, Cerisara, Bondioli, Faria, Garcia, Huberman, Lüdke, Mantovani, Nóvoa, Oliveira, Rosemberg, Tardif, among others, show that teachers are not able to name the knowledge they own, but they know what to teach the children and know where to find activities to be executed with them. Generally speaking, the teachers outlined the importance of executing an educative work and a necessary care of these children. Concerning the nursery care undertaken activities, the teachers reported they are not organized according to the contents. But concerning the degree of difficulty and the intentionality, which guides the age level of the nursery care children, the demands must be according to the child s development and the child´ s age specificity. A common aspect in the three teachers´ speech refers to the knowledge acquired in the professional practice by the exchange of knowledge with more experienced teachers, the main source of learning to teach in the nursery care.